2015
DOI: 10.1371/journal.pone.0127503
|View full text |Cite
|
Sign up to set email alerts
|

Zearalenone Mycotoxin Affects Immune Mediators, MAPK Signalling Molecules, Nuclear Receptors and Genome-Wide Gene Expression in Pig Spleen

Abstract: The toxicity of zearalenone (ZEA) was evaluated in swine spleen, a key organ for the innate and adaptative immune response. Weaned pigs were fed for 18 days with a control or a ZEA contaminated diet. The effect of ZEA was assessed on wide genome expression, pro- (TNF-α, IL-8, IL-6, IL-1β, IFN-γ) and anti-inflammatory (IL-10, IL-4) cytokines, other molecules involved in inflammatory processes (MMPs/TIMPs), as well as signaling molecules, (p38/JNK1/JNK2-MAPKs) and nuclear receptors (PPARγ/NFkB/AP-1/STAT3/c-JUN).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
55
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(64 citation statements)
references
References 60 publications
9
55
0
Order By: Relevance
“…2 ) . Similar effects have been reported, e.g., for the Fusarium mycotoxin zearalenone (ZEN), which likewise exerts immunosuppressive effects by suppressing NF-κB activity and expression of TNF-α, yet also increasing ROS levels in vitro (Ferrer et al 2009; Pistol et al 2015). Thus, no direct link might exist between AOH-induced ROS disbalance and NF-κB activity.…”
Section: Discussionsupporting
confidence: 64%
“…2 ) . Similar effects have been reported, e.g., for the Fusarium mycotoxin zearalenone (ZEN), which likewise exerts immunosuppressive effects by suppressing NF-κB activity and expression of TNF-α, yet also increasing ROS levels in vitro (Ferrer et al 2009; Pistol et al 2015). Thus, no direct link might exist between AOH-induced ROS disbalance and NF-κB activity.…”
Section: Discussionsupporting
confidence: 64%
“…Furthermore, ZEA is reported to be genotoxic in vitro (Zinedine et al, 2007), but IARC found limited evidence of ZEA carcinogenicity in animal models and has classified it together with DON in group 3, not classifiable (IARC, 2002). ZEA has also been shown to inhibit protein and DNA synthesis, induce lipid peroxidation, ROS generation, cell death (Abid-Essefi et al, 2004;Kouadio et al, 2005) and to modulate pro-inflammatory responses (Pistol et al, 2015;Pistol et al, 2014). ENNB is cytotoxic in several in vitro cell systems (Dornetshuber et al, 2007;Gammelsrud et al, 2012;Ivanova et al, 2006) and has been found to exert pro-inflammatory properties (Gammelsrud et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The ZEN-mediated induction of inflammation has already been studied in different tissues in immune cells [10,11], the spleen [57,58], the liver, [11] and the intestine [8,12,30,59]. We observed no signs of inflammation either at the gene expression level (interleukins 8, 17, 18, 22, TNF-α, interferon gamma, Lipocalin 2, S100A8, S100A12) or at the protein level (IL-17α, IL-8, serum amyloid A3 and alpha-acid glycoprotein alpha 1).…”
Section: Discussionmentioning
confidence: 99%